Ayurvedic management of scalp folliculitis - A case report - Vidya, H.C.; Hiremath, Nikhila B; Sajitha, K (Journal of Ayurveda and Holistic Medicine (JAHM), 2023)
Introduction: Folliculitis is a condition that involves the inflammation and damage of hair follicles, which are small openings in the skin that hold hair roots. While it can occur anywhere on the body, folliculitis develops most commonly in the scalp region, where the density of hair follicles is higher than in any other area. In Ayurveda, folliculitis can be managed based on the principles of Arunshika and Pittaja and Rakta Dushti. Materials and methods: A 38-year-old patient presented with complaints of skin lesions over the scalp region and pain for 2 years associated with hair loss. Virechana is an ideal method for Pitta and Rakta dushti. Result: The subject showed marked improvement in symptoms. Discussion: Virechana was administered to treat the root cause of the disease and the underlying cause with internal medicines for which the patient got significant relief from the symptoms.